Spatial variation in isotopic niches and trophic structure of Callinectes sapidus in the Balearic Islands - Esperança Perelló; Antoni Sureda; Antoni Box; Montserrat Compa; Samuel Pinya (Estuarine, Coastal and Shelf Science, 2026)

Biomarker responses in gills of Holothuria tubulosa from coastal waters of Eivissa Island (Western Mediterranean, Spain) to anthropogenic impact - Jessica Lombardo; Amanda Cohen-Sánchez; Antonio Box; Agostina Bartra; Trinidad García; Manuel Miró; Caterina Faggio; Silvia Tejada; Samuel Pinya; Antoni Sureda (Marine Pollution Bulletin, 2026)

Assessing heavy metal accumulation in the invasive blue crab (Callinectes sapidus): environmental and human health implications - Esperança Perelló; Samuel Pinya; Antoni Box; Antoni Sureda; Montserrat Compa (Environmental Science and Pollution Research, 2025)
Heavy metals are increasingly becoming a significant environmental concern, especially regarding food safety and security. This is especially concerning as the consumption of harvested marine species can pose potential health concerns. The arrival of the blue crab, Callinectes sapidus , to the Balearic Islands has led to the need to evaluate its environmental implications and potential as a food source as part of management efforts. In the present study, the concentrations of cadmium (Cd), lead (Pb), and mercury (Hg) in the muscle tissue of C. sapidus were evaluated at several locations in the Balearic Islands in the western Mediterranean Sea. A total of eighty-three blue crabs were examined (45 males and 38 females) and the concentrations of the heavy metals were evaluated. Regarding metal concentrations, overall, Hg was the most present followed by Cd and then Pb. Concentrations were also site dependent, with Es Grau having the highest Hg concentrations while in s’Albufereta the highest Cd concentrations were observed. Moreover, differences in metal accumulation were also observed between sexes, with juveniles and females exhibiting higher Cd concentrations than males. Furthermore, regarding potential human health concerns for consumption, the margin of exposure (MOE) for Pb were all above 1 and the estimated weekly ingestion (EWI) for Cd and Hg, were all below the established guidelines for food safety. These results highlight that the consumption of C. sapidus from the Balearic Islands does not currently pose a health risk the recreational fisheries sector. Considering these findings, the muscle tissue of C. sapidus is a valuable bioindicator for monitoring heavy metal levels, and continued site-specific monitoring is recommended for the coastal ecosystems of the Balearic Islands.

Exploring the impact of high salinity and parasite infection on antioxidant and immune systems in Coris julis in the Pityusic Islands (Spain) - Amanda Cohen-Sánchez; Antonio Box; José María Valencia; Samuel Pinya; Silvia Tejada; Antoni Sureda (Science of The Total Environment, 2024)

Presence and Potential Effects of Microplastics in the Digestive Tract of Two Small Species of Shark from the Balearic Islands - Susana Torres; Montserrat Compa; Antonio Box; Samuel Pinya; Antoni Sureda (Fishes, 2024)
In recent years, there has been an increase in the reporting of plastic pollution in the marine environment and its effects on marine animals, especially bony fish. However, the prevalence and effect, particularly concerning biomarkers of oxidative stress, in elasmobranchs remain underreported and unknown. In this study, microplastics were observed in two elasmobranch species from the Balearic Islands: the small-spotted catshark (Scyliorhinus canicula) with an average of 4.38 ± 1.77 items per individual, and the blackmouth catshark (Galeus melastomus) with an average of 8.31 ± 2.46 items per individual. Moreover, for the first time, antioxidant and pro-inflammatory responses were determined in the digestive tract of individuals of both species. Specifically, the activation of antioxidant defences, mainly superoxide dismutase activity and glutathione levels, was observed, while the pro-inflammatory marker myeloperoxidase activity was also greater in individuals with a high abundance of microplastic items. Additionally, a significant increase in glutathione S-transferase activity in catsharks with high microplastic ingestion was evidenced, suggesting that the detoxification process was activated. Overall, the results of this study highlight that both catshark species are ingesting microplastics, which, in turn, are causing physiological effects at a cellular level. Considering this, continued monitoring of these species should include the presence of microplastics, and the results from this study can serve as baseline data for future research.

Immune and Oxidative Stress Response of the Fish Xyrichthys novacula Infected with the Trematode Ectoparasite Scaphanocephalus sp. in the Balearic Islands - Amanda Cohen-Sánchez; Antoni Gabriel Sánchez-Mairata; José María Valencia; Antonio Box; Samuel Pinya; Silvia Tejada; Antoni Sureda (Fishes, 2023)
Global change produces substantial modification to the distribution and rhythm of infection of diseases in fish, favouring the introduction of new pathogens. Recently, the presence of black spot disease, associated with a digenean fluke of the genus Scaphanocephalus, has been observed in specimens of Xyrichthys novacula on the island of Ibiza (Balearic Islands). The aim of the present study was to evaluate the antioxidant and immune response in both the skin mucus and spleen of X. novacula depending on the degree of infection by Scaphanocephalus sp. The specimens were captured in a control area, without the presence of the parasite, and in an affected area, classifying the fish as low infection (1–15 spots) and high infection (>15 spots). As the degree of infection increased, a decrease in the body condition index was observed. The activity of the antioxidant enzymes in the mucus—catalase, superoxide dismutase and glutathione peroxidase—increased progressively with the degree of infection. This activation of antioxidant defences was not enough to prevent an increase in malondialdehyde levels, an indicator of oxidative damage, in the group with the highest infection. Similarly, an increase in immunological parameters—lysozyme, alkaline phosphatase, myeloperoxidase and immunoglobulins—was observed in mucus as infection increased. Regarding the spleen, only an increase in lysozyme activity and alkaline phosphatase in fish with a greater severity of infection was observed. In conclusion, as the severity of Scaphanocephalus sp. infection increased, it induced an immune and oxidative stress response in skin mucus, leading to a decrease in overall body condition. The potential health effects that the ectoparasite may have on X. novacula populations will require follow-up studies.

Ingestion of microplastics and microfibers by the invasive blue crab Callinectes sapidus (Rathbun 1896) in the Balearic Islands, Spain - Montserrat Compa; Esperança Perelló; Antoni Box; Victor Colomar; Samuel Pinya; Antoni Sureda (Environmental Science and Pollution Research, 2023)
The blue crab Callinectes sapidus Rathbun, 1896 is native to the western coasts of the Atlantic Ocean and is currently considered an invasive species in the Mediterranean Sea. In this study, we examined the stomach contents of C. sapidus to determine the frequency of occurrence of microplastics (MPs) and microfibers (MFs) in the Balearic Islands archipelago in the western Mediterranean Sea. A total of 120 individuals were collected from six locations between 2017 and 2020. Overall, 65.8% of the individuals had MPs and/or MFs particles with an average of 1.4 ± 1.6 particles ind. −1 of which an average of 1.0 ± 1.3 items ind. −1 were MFs and an average of 0.4 ± 0.8 items ind. −1 were MPs. In terms of type, fragments were the dominant type of MPs and the most common size of items ranged from between 0.5 and 1 mm (40%) followed by 1–5 mm (31%). The most prevalent polymers were low-density polyethylene (39%) and high-density polyethylene (26%). In terms of links to human activities, MP ingestion was positively correlated with an increase in drain pipes, whereas MF ingestion was positively correlated with an increase in sewage pipelines, providing evidence of potential sources and the bioavailability of these particles in various environments. This study confirms the widespread presence of MP and MF particles, even in areas that are currently managed under different protection statuses, in the stomach contents of invasive blue crab species throughout coastal communities.

Black spot disease related to a trematode ectoparasite causes oxidative stress in Xyrichtys novacula - Amanda Cohen-Sánchez; José María Valencia; Antonio Box; Antònia Solomando; Silvia Tejada; Samuel Pinya; Gaetano Catanese; Antoni Sureda (Journal of Experimental Marine Biology and Ecology, 2023)

First detection of microplastics in Xyrichtys novacula (Linnaeus 1758) digestive tract from Eivissa Island (Western Mediterranean) - Amanda Cohen-Sánchez; Antònia Solomando; Samuel Pinya; Silvia Tejada; José María Valencia; Antonio Box; Antoni Sureda (Environmental Science and Pollution Research, 2022)
Plastic waste and its ubiquity in the oceans represent a growing problem for marine life worldwide. Microplastics (MPs) are ubiquitous in the sea and easily enter food webs. Xyrichtys novacula L. is one of the main target species of recreational fishing in the Balearic Islands, Spain. In the present study, the quantity of MPs in gastrointestinal tracts of X. novacula from two different areas (a marine protected area (MPA) and a non-protected area) of Eivissa Island (in the Balearic archipelago) has been assessed, as well as MPs evaluation within the sediment of both areas. The results showed that over 80% of sampled individuals had MPs in their gut with an average of 3.9 ± 4.3 plastic items/individual. Eighty percent of these plastics were fibres, while the rest were fragments. Although the sediment of the non-protected area had a significant higher presence of MPs, no significant differences in the number of MPs were observed in X. novacula from both areas. The µ-FT-IR analysis showed that the main polymers in the sediments were polycarbonate (PC) and polypropylene (PP), whereas in the digestive tract of fish PC, PP, polyethylene, polystyrene and polyester. In conclusion, practically all X. novacula specimens presented MPs in their digestive tract regardless if the capture zone was in a MPAs or not. These results highlight the ubiquity of MPs in coastal marine areas, and further studies might be necessary to evaluate further implications of MP presence in this species.

Perkinsus mediterraneus infection induces oxidative stress in the mollusc Mimachlamys varia - Antonio Box; Xavier Capó; Silvia Tejada; Antoni Sureda; Laia Mejías; José María Valencia (Journal of Fish Diseases, 2020)
Perkinsus mediterraneus is a protozoan parasite that can cause marine mollusc diseases known as perkinsosis being a serious threat for clam cultures worldwide. The aim of the present study was first to determine the Perkinsus species infecting the variegated scallop Mimachlamys varia and then to evaluate the existence of oxidative stress in gills of M. varia according to different degrees of infection. DNA sequencing confirmed that P. mediterraneus was the species infecting M. varia . ROS production was progressively increasing with the degree of infection although the differences were only significant in the high‐infected group. Low degree of infection significantly increased superoxide dismutase (SOD) and glutathione S ‐transferase (GST) activities and nitrite levels with respect to the control group. In the high‐infected group, a significant increase was evidenced in all analysed enzymes, catalase, SOD, glutathione reductase and GST. Non‐significant differences in MDA levels were observed between the control and low‐infected groups; however, a significant increase in MDA levels was observed in the high‐infected group. In conclusion, the infection by Perkinsus mediterraneus in M. varia induces oxidative stress and an antioxidant response directly related to the infection degree that can contribute to the pathogenicity of the infection.